Effect of natural antioxidants in controlling alkaline contaminant materials (ACM) in heated palm olein - Jaswir, Irwandi; Che Man, Yaakob B.; Kitts, David D. (2000)
A spectrophotometric-based method was developed to determine the changes in alkaline contaminant materials (ACM) of natural antioxidant-treated, refined, bleached and deodorized (RBD) palm olein during 5-day deep-fat frying of potato chips. Results showed that the ACM contents in RBD palm olein could be determined spectrophotometrically at 540 nm. Oleoresin rosemary extract, sage extract and citric acid significantly (P < .05) lowered the ACM content in oil during 5-day deep-fat frying of potato chips. A combination of 0.087% oleoresin rosemary extract, 0.072% sage extract and 0.025% citric acid was required to achieve the minimum level of ACM after 5-day frying. (C) 2000 Published by Elsevier Science Ltd.